Scale Evolution of Higher Vocational Education and Measurement of Education Opportunity Difference Based on the Expansion Effect - Li, Liyang (International Journal of Emerging Technologies in Learning (iJET), 2023)
Scale expansion of higher vocational education requires scientific instructions, therefore figuring out the spatial and temporal evolution laws of higher education is a meaningful work for realizing the scale expansion of quality-oriented higher vocational education. However, existing studies have neither discussed the effect of such instructions on the rewards of higher vocational education, nor considered the comprehensive influence of the promotive and instructive effect of market-oriented and society-oriented employment of high vocational education on its heterogeneous rewards. To fill in these research blanks, this paper studied the evolution of the scale of higher vocational education and the difference in educational opportunities based on the expansion effect. At first, this paper constructed a scale expansion effect model of higher vocational education to explore the reward mechanism of scale expansion of higher vocational education in the labor market. Then, the paper distinguished the different levels of higher vocational education, and analyzed the evolution mechanism of the unfairness degree of students or workers acquiring different-level higher vocational education opportunities during the scale expansion process of higher vocational education. At last, the experimental results and analysis results were given.